Thinking Through Circus. - Lievens, Bauke; Kann, Sebastian; Ketels, Quintijn; Focquet, Vincent (Gent : Art Paper Editions, 2019)
Thinking Through Circus was published in the framework of The Circus Dialogues, a two-year artistic research project (2018-2020) initiated by Bauke Lievens, an affiliated researcher and professor at KASK School of Arts. Quintijn Ketels and Sebastian Kann were the asociated researchers, accompanied by VIndent Focquet. The Cirucus Dialogues was financed by the Arts Research Fund of University College Ghent (BE). The publication of this book has been co-funded with the support of the Flemish Government (Department of Culture, Youth and Media).
boek
Keywords: Lievens, Bauke